A revisit to the incremental capital-output ratio: the case of Asian economies and Thailand. (1st January 2014) - Taguchi, Hiroyuki; Lowhachai, Suphannada
This paper aims to examine the trend in the incremental capital-output ratio (ICOR) and its relationship with per capita GDP and GDP growth rate by utilising the panel data of a number of Asian economies and the historical time-series data of Thailand. It might be significant to know the linkage between growth and investment through the ICOR level, since Asian economies have faced serious needs for heavy investments to attain a targeted growth. The panel-data analysis confirmed that the gross ICOR had a positive correlation with per capita GDP and a negative association with GDP growth rate as expected in a theoretical model. The time-series analysis verified that the net ICOR was positively correlated with per capita GDP. Both analyses showed that industrial shares did not affect the level of the gross and net ICORs.